EU-1 / ZSM-12 eutectic molecular sieve and synthesis method thereof

By using composite template agents and oxysilane materials, the EU-1/ZSM-12 eutectic molecular sieve with small nanocrystals has been solved, and the existing molecular sieve has large grain size, complex preparation and low activity are achieved, and high efficiency is achieved catalytic and adsorption effects.

CN119461406APending Publication Date: 2025-02-18CHINA CATALYST HLDG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411465903.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing ZSM-12 and EU-1 molecular sieves have large grain sizes, complex preparation and low activity, which limits their application in catalytic reactions.

Method used

Use methyl triethylammonium hydroxide and 1,6-bis(methylpyrrolidine)hexane dihydroxide as composite template agents, low molecular weight alcohol amine organic matter as additive additives, and oxysilane as silicon source , EU-1/ZSM-12 eutectic molecular sieve of nanocrystalline crystallization reaction was synthesized.

Benefits of technology

The obtained EU-1/ZSM-12 eutectic molecular sieve has relatively high crystallinity, small grain size, simple preparation method, high catalytic activity, and is suitable for catalysis and adsorption applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461406A_ABST
    Figure CN119461406A_ABST
Patent Text Reader

Abstract

The invention discloses a nano small-grain EU-1 / ZSM-12 eutectic molecular sieve and a synthesis method thereof. The eutectic molecular sieve has a single grain length of less than or equal to 300nm, a total specific surface area of more than or equal to 350m < 2 > / g and a total pore volume of more than or equal to 0.24 cm < 3 > / g, the weight percentage of the EU-1 molecular sieve is 5-90%, the weight percentage of the ZSM-12 molecular sieve is 10-95%, and the molar ratio range of silicon oxide to aluminum oxide in the molecular sieve is 20-200. The preparation method comprises the following steps: carrying out hydrothermal crystallization on a mixture of organosilane, an aluminum source, an alkali source, 1, 6-bis (methylpyrrolidine) hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, an alcohol amine organic auxiliary agent AIDS and deionized water H2O to obtain the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a EU-1 / ZSM-12 eutectic molecular sieve with nano-sized crystal particles and a synthesis method thereof, belonging to the technical field of inorganic material synthesis. Background Art

[0002] ZSM-12 molecular sieve is a MTW structure molecular sieve with one-dimensional twelve-membered ring (0.57nm×0.61nm) straight pores. The pore size can effectively realize the catalytic conversion of most organic molecules. Because it has no super cage structure and cross pores, the diffusion of multi-branched products is not restricted, and it has high acid resistance, good thermal stability and hydrothermal stability. ZSM-12 molecular sieve has a pore size between medium-pore and large-pore zeolites, which can effectively realize the catalytic conversion of most organic molecules. It has good catalytic performance for reactions such as hydrocarbon cracking, isomerization, dehydration and reforming. It has good application prospects for the catalytic conversion reaction of heavy components and macromolecular crude oil in the fields of petroleum refining and chemical industry.

[0003] EU-1 molecular sieve is a type of molecular sieve with EUO topological structure. Its crystal structure has a one-dimensional 0.54nm×0.41nm ten-membered ring pore in the

[100] direction, and there are deep 0.81nm twelve-membered ring pores on both sides of the ten-membered ring pore. 0.68nm×0.58nm side pockets. Due to the pore structure characteristics of EU-1 molecular sieve, it is a promising type of catalyst carrier and acidic active component. It is used as a bifunctional catalyst for the preparation of the acidic component of the isomerization catalyst of C8 aromatics. It shows good activity and selectivity in the catalytic reaction of hydroisomerization of C8 aromatics and isopropylation of benzene, and is known as the first choice of the new generation of xylene isomerization catalytic materials.

[0004] Co-crystallized molecular sieve refers to a co-crystallization formed by two or more molecular sieves, or a composite crystal having two or more molecular sieve structural characteristics, which often has properties different from a single molecular sieve or a corresponding molecular sieve mechanical mixture. Because the eutectic molecular sieve has multiple structures and superposition functions, it avoids the defects of a single pore structure system and has great advantages in molecular adsorption and diffusion. EU-1 and ZSM-12 molecular sieves are both single 1-dimensional mesopore and macropore molecular sieves, respectively, so the EU-1 / ZSM-12 eutectic molecular sieve has the characteristics of both 1-dimensional mesopores and macropores. CN116022821A has a composite molecular sieve with EUO structure and MTW structure, and its preparation method and application, the EUO structure and MTW structure composite molecular sieve use silica-alumina gel as a composite silica-alumina source, silica-alumina gel, inorganic base, template agent such as 1,4-bis (N-methylpyrrolidine) butane hydroxide, water as raw materials, crystallization obtained. Since the ZSM-12 molecular sieves synthesized by these methods have large grain sizes and only regular micropores, the internal surface utilization and active site density are low, which limits the diffusion and conversion of macromolecular compounds in the pores. Therefore, their catalytic activity is low and they are easily deactivated by carbon deposition, which greatly limits their industrial applications. Nano molecular sieves have the characteristics of large pore volume and specific surface area, high activity and stability, which can effectively improve the diffusion performance of the product and inhibit the occurrence of carbon deposition.

[0005] The purpose of the present invention is to overcome the problem of single pore structure of molecular sieves in the prior art, and to provide a EU-1 / ZSM-12 eutectic molecular sieve and its preparation method, application and catalyst, wherein the EU-1 / ZSM-12 eutectic molecular sieve has a multi-level pore structure. Summary of the invention

[0006] The invention aims to provide a nano-sized small-grain EU-1 / ZSM-12 eutectic molecular sieve and a synthesis method thereof. Methyltriethylammonium hydroxide and 1,6-bis(methylpyrrolidine)hexane dihydroxide composite template agents, low molecular weight alcohol amine organic matter as additives, and oxysilanes as silicon sources are used. The synthesized EU-1 / ZSM-12 eutectic molecular sieve has high relative crystallinity and an adjustable ratio of two-phase molecular sieves, thereby solving the problem that the prior art cannot synthesize the EU-1 / ZSM-12 eutectic molecular sieve.

[0007] The purpose of the present invention is to overcome the problems of the prior art that ZSM-12 and EU-1 molecular sieves are large in size, complex in preparation and low in activity, and to provide a EU-1 / ZSM-12 eutectic molecular sieve and a preparation method and application thereof, a catalyst composition and application thereof. The EU-1 / ZSM-12 eutectic molecular sieve has the characteristics of small crystal size, simple preparation method and high activity.

[0008] In order to solve the above technical problems, the technical solution of the present invention is: a nano-sized EU-1 / ZSM-12 eutectic molecular sieve, the XRD phase of the EU-1 / ZSM-12 eutectic molecular sieve having characteristic peaks at 7.45±0.2°, 7.91±0.2°, 8.70±0.2°, 19.01±0.2°, 20.52±0.2°, 20.90±0.2°, 22.14±0.2°, 22.96±0.2°, 23.22±0.2°, 23.68±0.2°, 25.78±0.2°, and 27.20±0.2°.

[0009] The nano-sized EU-1 / ZSM-12 eutectic molecular sieve has a grain length of ≤300nm and a total specific surface area of ​​≥350 m 2 / g, total pore volume ≥ 0.24 cm 3 / g, in the eutectic molecular sieve, the weight percentage of EU-1 molecular sieve is 5-90%, the weight percentage of ZSM-12 molecular sieve is 10-95%, and the molar ratio of silicon oxide to aluminum oxide in the eutectic molecular sieve is in the range of 20-200.

[0010] The eutectic molecular sieve is obtained by mixing organic silane, aluminum source, alkali source, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, organic auxiliary agent AIDS and deionized water, and then sequentially subjecting the mixture to aging, hydrothermal crystallization reaction, filtration, washing, drying, roasting, ammonium ion exchange, drying and roasting.

[0011] The organosilane is calculated as SiO2, the aluminum source is calculated as Al2O3, and the alkali source is calculated as Na2O. The molar ratio of Na2O:SiO2:Al2O3:OSDA1:OSDA2:AIDS:H2O is: (0.05~0.25):1.0:(0.005~0.05):(0.0015~0.27):(0.01~0.3):(0.001~0.01):(10~50).

[0012] The synthesis process of the EU-1 / ZSM-12 eutectic molecular sieve with nano-sized crystals is as follows: S1, preparing a mixed sol: mixing organic silane, aluminum source, alkali source, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, organic auxiliary agent (in terms of AIDS) and deionized water H2O uniformly to obtain a mixed sol; in the mixed sol, the alkali source is calculated as Na2O, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is nNa2O:nSiO2:nAl2O3:nOSDA1:nOSDA2:nAIDS:nH2O = (0.05~0.25):1.0:(0.005~0.05):(0.0015~0.27):(0.01~0.3):(0.001~0.01):(10~50); S2, placing the mixed sol obtained in step S1 in a crystallization kettle, aging at 80-120°C for 8-36 hours, then heating to 150-200°C for crystallization for 24-168 hours, separating the solid product after complete crystallization, washing the solid product, drying at 80-150°C for 8-36 hours, and calcining at 500-800°C for 2-20 hours to remove the organic template, thereby obtaining the original powder of the molecular sieve; S3, the EU-1 / ZSM-12 eutectic molecular sieve powder obtained in step S2 is subjected to ammonium ion exchange to remove Na + ions, and the product was dried at 100-140 °C for 12-48 h and calcined at 500-800 °C for 1-10 h to obtain H-type EU-1 / ZSM-12 eutectic molecular sieve.

[0013] Further, the organosilane described in the present invention is any one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, ethyltriethoxysilane, vinyltriethoxysilane, triethoxysilane, propyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane, methyltriethoxysilane, trimethoxysilane, propyltriethoxysilane, methylvinyldimethoxysilane, methyldimethoxysilane, isobutyltriethoxysilane, diisopropyldimethoxysilane, and isobutylisopropyldimethoxysilane, preferably any one of methyl orthosilicate, ethyl orthosilicate, propylorthosilicate, butylorthosilicate, trimethoxysilane, and triethoxysilane.

[0014] Furthermore, the synthesis method described in the present invention is characterized in that the aluminum source described in step S1 is any one of pseudo-boehmite, sodium aluminate, aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, aluminum isopropoxide or aluminum sol, or a mixture of two or more in any proportion.

[0015] Furthermore, the synthesis step of the present invention is characterized in that the alkali source described in step S1 is any one of NaOH, KOH, Na2O2, Na2CO3, and NaHCO3, or a mixture of two or more of them in any proportion.

[0016] Furthermore, according to the synthesis process steps of the present invention, the method for synthesizing the organic template 1,6-bis(methylpyrrolidine)hexane dihydroxide used in step S1 is characterized in that: N-methylpyrrolidine, 1,6-dibromohexane and ethanol are contacted and reacted at a mass ratio of 1:(0.90~2.0):(3~10) at 25~65°C for 2~8 hours, then cooled and filtered, and vacuum dried to obtain a solid product, which is then prepared into a solution and electrolytically concentrated to obtain an aqueous solution of 1,6-bis(methylpyrrolidine)hexane dihydroxide.

[0017] Further, in the synthesis process steps of the present invention, the alcoholamine organic auxiliary agent AIDS added in step S1 is any one or more of ethanolamine, N,N-dimethylethanolamine, N-methylmonoethanolamine, N-ethylethanolamine, and N, N-dimethylisopropanolamine.

[0018] Further, the synthesis process steps of the present invention are characterized in that in step S3, the NH 4+ Ionic solution refers to an aqueous solution of ammonium salt, which is any one of ammonium chloride, ammonium sulfate, ammonium nitrate, ammonium carbonate, and ammonium acetate, or a mixture of two or more of them in any proportion; in the aqueous solution of ammonium salt, the concentration of ammonium salt is 0.1~3.0 mol / L, and ion exchange is carried out 1~3 times with molecular sieve solid powder at a solid-liquid ratio of 1: (4~40) in a water bath at 60~100 ℃.

[0019] Through the above technical solution, the present invention has the following beneficial effects: 1) The EU-1 / ZSM-12 eutectic molecular sieve provided by the present invention comprises a morphology of nanoparticle agglomerates, and the eutectic molecular sieve synthesized in the preparation method thereof does not require the addition of seed crystals and has a good crystallization effect.

[0020] 2) Synthesize eutectic molecular sieves containing two different pore structures, provide different levels of pore structures, which are conducive to adapting to different molecular reactions. By mutually adjusting the pore structure and acidity between them, their catalytic characteristics can be fully exerted.

[0021] 3) The catalytic activity of the EU-1 / ZSM-12 eutectic molecular sieve with a one-dimensional linear pore structure is relatively low in most reactions compared with molecular sieves with three-dimensional or two-dimensional pores such as USY and Beta, but because it has no supercage structure and cross-pores, the diffusion of multi-branched products is not restricted. 4) Since the eutectic molecular sieve synthesized by the present invention belongs to a zeolite molecular sieve, the zeolite molecular sieve itself has a special pore structure, excellent adsorption performance and abundant surface acid sites. 5) The present invention provides a new EU-1 / ZSM-12 eutectic molecular sieve with a unique chemical composition and XRD diffraction pattern. The molecular sieve contains a multi-level pore structure, a wide distribution range of strong acids and weak acids, and has potential advantages in applications such as catalysis and adsorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Figure 1 This is the XRD phase diagram of the EU-1 / ZSM-12 eutectic molecular sieve synthesized in Example 1; Figure 2 This is the XRD phase diagram of the EU-1 / ZSM-12 eutectic molecular sieve synthesized in Example 2; Figure 3 This is the XRD phase diagram of the EU-1 / ZSM-12 eutectic molecular sieve synthesized in Example 3; Figure 4 This is the XRD phase diagram of the EU-1 / ZSM-12 eutectic molecular sieve synthesized in Example 4; Figure 5 This is a SEM analysis image of the EU-1 / ZSM-12 eutectic molecular sieve synthesized in Example 1; Figure 6 This is a SEM analysis image of the EU-1 / ZSM-12 eutectic molecular sieve synthesized in Example 2; Figure 7 This is a SEM analysis image of the EU-1 / ZSM-12 eutectic molecular sieve synthesized in Example 3; Figure 8 This is the SEM analysis picture of the EU-1 / ZSM-12 eutectic molecular sieve synthesized in Example 4. DETAILED DESCRIPTION

[0023] The embodiments of the present invention and the effects produced are further illustrated by examples and comparative examples, but the protection scope of the present invention is not limited to the contents listed in the examples.

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] The pore volume of the samples was measured on a Micromeritics ASAP2460 physical adsorption instrument. Before the test, the samples were vacuum treated at 200°C for 6 hours, and then the N2 adsorption and desorption isotherms were measured at liquid nitrogen temperature. The micropore volume of the samples was calculated by the t-plot method.

[0026] The samples were characterized by XRD using a PANalytical Xpert Pro diffractometer with Cu Kα radiation (λ=0.15406 nm), a tube voltage of 45 kV, a tube current of 40 mA, a scanning range of 5°~55°, a step of 0.026°, and a step time of 17.34 ms.

[0027] The composition of the samples was determined using a PANalytical Axios series X-ray fluorescence spectrometer (XRF). The sample was prepared using a tablet pressing method and the measurement conditions were an end-window rhodium target, a tube voltage of 50 kV, and a tube current of 50 mA.

[0028] A Hitachi thermal field emission scanning electron microscope SU5000 was used for detection in the backscattering mode, with the beam current adjusted to “standard”, the acceleration voltage selected to be 10 kV, and the magnification 5k~50k.

[0029] For the eutectic molecular sieve of the present invention, the lattice plane spacing (d) is calculated from the XRD pattern using the powder method of X-ray diffraction analysis, and compared and identified with the data collected in the XRD database of the International Society of Synthetic Zeolites or the PDF (Powder Diffraction File) of ICDD (International Centre for Diffraction Data).

[0030] The pure phase and high relative crystallinity EU-1 molecular sieve and ZSM-12 molecular sieve were mechanically uniformly mixed and ground according to the mass ratio of 10:90, 20:80, 30:70, 40:60, 50:50, 60:40, 70:30, and the XRD characteristic peak area was measured. The five characteristic peaks at 2θ angles of 7.9±0.1, 20.5±0.1, 22.2±0.1, 23.8±0.1, and 27.2±0.1 corresponded to the EU-molecular sieve, and the total area was related to the mass percentage of EU-1; ​​the five characteristic peaks at 2θ angles of 7.4±0.1, 20.8±0.1, 22.8±0.1, 25.7±0.1, and 35.6±0.1 corresponded to the ZSM-12 molecular sieve, and the total area was related to the mass percentage of ZSM-12. Thus, a function curve of the EU-1 / ZSM-12 peak area ratio and the EU-1 / ZSM-12 molecular sieve mass ratio was obtained, which was used as a reference curve to calculate the relative ratio of the two molecular sieves in the sample to be tested.

[0031] Example 1: Synthesis of organic template 1,6-bis(methylpyrrolidine)hexane dihydroxide: 1) To a 1L flask containing 50g of N-methylpyrrolidine (99%) and 250mL of ethanol, 50g of 1,6-dibromohexane (99%) was added. The reaction medium was stirred and heated at reflux at 50°C for 5 hours. The mixture was then cooled to ambient temperature and filtered. The mixture was poured into 300mL of cold diethyl ether, and the precipitate formed was then filtered and washed with 100mL of diethyl ether. The solid obtained was recrystallized from the ethanol / ether mixture. The solid obtained was dried under vacuum for 12 hours to obtain a solid substance, namely 1,6-bis(methylpyrrolidine)hexane bromide.

[0032] 2) The above-mentioned 1,6-bis(methylpyrrolidine)hexane bromide was dissolved in water to prepare an aqueous solution with a concentration of 25wt%, and placed in a feed liquid storage tank. NaOH was dissolved in water to prepare an aqueous solution with a concentration of 0.18wt%, and placed in a pole liquid storage tank. Ammonia water with a concentration of 2.5wt% was used as a neutralizing solution, and the neutralizing solution was placed in a neutralizing solution storage tank. The prepared 1,6-bis(methylpyrrolidine)hexane bromide aqueous solution was sent to the alkali chamber of the bipolar membrane electrodialysis device, the pole liquid was sent to the anode chamber and cathode chamber of the bipolar membrane electrodialysis device, and the neutralizing solution was sent to the acid chamber of the bipolar membrane electrodialysis device. Then, direct current was applied between the anode and cathode of the bipolar membrane electrodialysis device, and bipolar membrane electrodialysis was performed continuously for 70 hours at a temperature of 35°C, with a current density of 4A / dm 2 An aqueous solution containing 1,6-bis(methylpyrrolidino)hexane dihydroxide was obtained.

[0033] Example 2: Preparation of eutectic molecular sieve EZ12-1 1) Preparation of mixed sol: Methyl orthosilicate, sodium aluminate, NaOH, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, ethanolamine (in terms of AIDS) and deionized water H2O are uniformly mixed to obtain a mixed sol; in the mixed sol, the alkali source is calculated as Na2O, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is nNa2O:nSiO2:nAl2O3:nOSDA1:nOSDA2:nAIDS:nH2O =0.15:1:0.006667:0.0018:0.0282:0.001:25.

[0034] 2) The mixed sol obtained in step 1) is placed in a crystallization kettle, aged at 105°C for 24 hours, then heated to 170°C for crystallization for 72 hours, and after complete crystallization, a solid product is separated. The solid product is washed, dried at 120°C for 24 hours, and calcined at 550°C for 15 hours to remove the organic template, thereby obtaining the original powder of the molecular sieve; the obtained product is analyzed by powder XRD and SEM, and the XRD pattern of the original powder after synthesis is shown in Figure 1 The product has complete characteristic peaks of EU-1 and ZSM-12 molecular sieves and is determined to be EU-1 / ZSM-12 eutectic molecular sieve. The SEM image of the product is shown in Figure 5 In the composite molecular sieve, small crystals <300 nm are agglomerated, and the overall dispersion is good. XRD diffraction quantitative analysis shows that the weight percentage of EU-1 structure molecular sieve in the composite molecular sieve is 5.8%, and the weight percentage of ZSM-12 structure molecular sieve is 94.2%.

[0035] 3) The EU-1 / ZSM-12 eutectic molecular sieve powder obtained in step 2) was exchanged with 0.5 mol / L NH4Cl solution at a solid-liquid ratio of 1:30 at 90°C for 4 h, and the ammonium ion exchange was repeated twice. The Na2O% content in the molecular sieve product was less than 0.1%, and an H-type small-grain EU-1 / ZSM-12 eutectic molecular sieve was obtained. The molar ratio of silicon oxide to aluminum oxide was 147. The physical and chemical characterization results are shown in Table 1, and it is recorded as EZ12-1.

[0036] Example 3: Preparation of eutectic molecular sieve EZ12-2 1) Preparation of mixed sol: Ethyl orthosilicate, pseudo-boehmite, NaOH, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, N,N-dimethylethanolamine (in terms of AIDS) and deionized water H2O are uniformly mixed to obtain a mixed sol; in the mixed sol, the alkali source is calculated as Na2O, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is nNa2O:nSiO2:nAl2O3:nOSDA1:nOSDA2:nAIDS:nH2O =0.18:1:0.011521:0.015:0.035:0.003:45.

[0037] 2) The mixed sol obtained in step 1) is placed in a crystallization kettle, aged at 90°C for 32 hours, then heated to 175°C for crystallization for 60 hours. After complete crystallization, a solid product is separated. The solid product is washed, dried at 85°C for 36 hours, and calcined at 650°C for 8 hours to remove the organic template to obtain the original powder of the molecular sieve; the obtained product is analyzed by powder XRD and SEM. The XRD pattern of the original powder after synthesis is shown in Figure 2 The product has complete characteristic peaks of EU-1 and ZSM-12 molecular sieves and is determined to be EU-1 / ZSM-12 eutectic molecular sieve. The SEM image of the product is shown in Figure 6 In the composite molecular sieve, small crystals <300 nm are agglomerated, and the overall dispersion is good. XRD diffraction quantitative analysis shows that the weight percentage of EU-1 structure molecular sieve in the composite molecular sieve is 29.8%, and the weight percentage of ZSM-12 structure molecular sieve is 70.2%.

[0038] 3) The EU-1 / ZSM-12 eutectic molecular sieve powder obtained in step 2) was exchanged with 1.5 mol / L NH4Cl solution at a solid-liquid ratio of 1:20 at 80°C for 6 h, and the ammonium ion exchange was repeated twice. The Na2O% content in the molecular sieve product was less than 0.1%, and an H-type small-grain EU-1 / ZSM-12 eutectic molecular sieve was obtained. The molar ratio of silicon oxide to aluminum oxide was 84.30. The physical and chemical characterization results are shown in Table 1 and are recorded as EZ12-2.

[0039] Example 4: Preparation of eutectic molecular sieve EZ12-3 1) Preparation of mixed sol: Propyl orthosilicate, aluminum isopropoxide, NaOH, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, N-methylmonoethanolamine (in terms of AIDS) and deionized water H2O are uniformly mixed to obtain a mixed sol; in the mixed sol, the alkali source is calculated as Na2O, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is nNa2O:nSiO2:nAl2O3:nOSDA1:nOSDA2:nAIDS:nH2O =0.05:1:0.046512:0.096:0.024:0.005:40.

[0040] 2) The mixed sol obtained in step 1) is placed in a crystallization kettle, aged at 120 °C for 12 hours, then heated to 165 °C for crystallization for 120 hours. After the crystallization is complete, the solid product is separated. The solid product is washed, dried at 105 °C for 20 hours, and calcined at 600 °C for 6 hours to remove the organic template to obtain the original powder of the molecular sieve. The obtained product is analyzed by powder XRD and SEM. The XRD diagram of the original powder after synthesis shows Figure 3 The product has complete characteristic peaks of EU-1 and ZSM-12 molecular sieves and is determined to be EU-1 / ZSM-12 eutectic molecular sieve. The SEM image of the product is shown in Figure 7 In the composite molecular sieve, small crystals <300 nm are agglomerated, and the overall dispersion is good. XRD diffraction quantitative analysis shows that the weight percentage of EU-1 structure molecular sieve in the composite molecular sieve is 79.8%, and the weight percentage of ZSM-12 structure molecular sieve is 20.2%.

[0041] 3) The EU-1 / ZSM-12 eutectic molecular sieve powder obtained in step 2) was exchanged with 2 mol / L NH4Cl solution at a solid-liquid ratio of 1:15 at 70 °C for 8 h, and the ammonium ion exchange was repeated twice. The Na2O% content in the molecular sieve product was less than 0.1%, and H-type small-grain EU-1 / ZSM-12 eutectic molecular sieve was obtained. The molar ratio of silicon oxide to aluminum oxide was 20.4. The physical and chemical characterization results are shown in Table 1 and are recorded as EZ12-3.

[0042] Example 5: Preparation of eutectic molecular sieve EZ12-4 1) Preparation of mixed sol: n-butyl orthosilicate, aluminum chloride, NaOH, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, N-ethylethanolamine (in terms of AIDS) and deionized water H2O are uniformly mixed to obtain a mixed sol; in the mixed sol, the alkali source is calculated as Na2O, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is nNa2O:nSiO2:nAl2O3:nOSDA1:nOSDA2:nAIDS:nH2O =0.08:1:0.018182:0.018:0.012:0.007:35; 2) The mixed sol obtained in step 1) is placed in a crystallization kettle, aged at 85°C for 30 hours, then heated to 180°C for crystallization for 48 hours. After complete crystallization, a solid product is separated. The solid product is washed, dried at 90°C for 36 hours, and calcined at 500°C for 20 hours to remove the organic template to obtain the original powder of the molecular sieve. The obtained product is analyzed by powder XRD and SEM. The XRD pattern of the original powder after synthesis is shown in Figure 4 The product has complete characteristic peaks of EU-1 and ZSM-12 molecular sieves and is determined to be EU-1 / ZSM-12 eutectic molecular sieve. The SEM image of the product is shown in Figure 8 In the composite molecular sieve, small crystals <300 nm are agglomerated, and the overall dispersion is good. XRD diffraction quantitative analysis shows that the weight percentage of EU-1 structure molecular sieve in the composite molecular sieve is 59.6%, and the weight percentage of ZSM-12 structure molecular sieve is 40.4%.

[0043] 3) The EU-1 / ZSM-12 eutectic molecular sieve powder obtained in step 2) was exchanged with 2.5 mol / L NH4Cl solution at a solid-liquid ratio of 1:5 at 60 °C for 8 h, and the ammonium ion exchange was repeated twice. The Na2O% content in the molecular sieve product was less than 0.1%, and an H-type small-grain EU-1 / ZSM-12 eutectic molecular sieve was obtained. The molar ratio of silicon oxide to aluminum oxide was 52.90. The physical and chemical characterization results are shown in Table 1 and are recorded as EZ12-4.

[0044] Example 6: Preparation of eutectic molecular sieve EZ12-5 1) Preparation of mixed sol: trimethoxysilane, aluminum nitrate, NaOH, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, N, N-dimethylisopropanolamine (in terms of AIDS) and deionized water H2O are uniformly mixed to obtain a mixed sol; in the mixed sol, the alkali source is calculated as Na2O, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is nNa2O:nSiO2:nAl2O3:nOSDA1:nOSDA2:nAIDS:nH2O=0.12:1:0.015385:0.0825:0.0675:0.009:30; 2) The mixed sol obtained in step 1) is placed in a crystallization kettle, aged at 110 °C for 8 hours, then heated to 155 °C for crystallization for 160 hours. After complete crystallization, the solid product is separated, washed, dried at 135 °C for 12 hours, and calcined at 800 °C for 3 hours to remove the organic template agent, and the original powder of the molecular sieve is obtained; the obtained product is analyzed by powder XRD and SEM, and the XRD phase of the original powder after synthesis shows that it has complete characteristic peaks of EU-1 and ZSM-12 molecular sieves, and it is determined to be EU-1 / ZSM-12 eutectic molecular sieve. XRD diffraction quantitative analysis shows that the weight percentage of EU-1 structure molecular sieve in the composite molecular sieve is 54.7%, and the weight percentage of ZSM-12 structure molecular sieve is 45.3%.

[0045] 3) The EU-1 / ZSM-12 eutectic molecular sieve powder obtained in step 2) was exchanged with 1.0 mol / L NH4Cl solution at a solid-liquid ratio of 1:25 at 65°C for 8 h, and the ammonium ion exchange was repeated twice. The Na2O% content in the molecular sieve product was less than 0.1%, and an H-type small-grain EU-1 / ZSM-12 eutectic molecular sieve was obtained. The molar ratio of silicon oxide to aluminum oxide was 63.10. The physical and chemical characterization results are shown in Table 1, and it is recorded as EZ12-5.

[0046] Example 7: Preparation of eutectic molecular sieve EZ12-6 1) Preparation of mixed sol: triethoxysilane, aluminum sulfate, NaOH, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, triethoxysilane (in terms of AIDS) and deionized water H2O are uniformly mixed to obtain a mixed sol; in the mixed sol, the alkali source is calculated as Na2O, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is nNa2O:nSiO2:nAl2O3:nOSDA1:nOSDA2:nAIDS:nH2O =0.1:1:0.032787:0.03:0.25:0.004:15.

[0047] 2) The mixed sol obtained in step 1) is placed in a crystallization kettle, aged at 100°C for 20 hours, then heated to 160°C for crystallization for 144 hours. After complete crystallization, the solid product is separated, washed, dried at 140°C for 10 hours, and calcined at 700°C for 4 hours to remove the organic template agent, and the original powder of the molecular sieve is obtained; the obtained product is analyzed by powder XRD and SEM, and the XRD phase of the original powder after synthesis shows that it has complete characteristic peaks of EU-1 and ZSM-12 molecular sieves, and it is determined to be EU-1 / ZSM-12 eutectic molecular sieve. XRD diffraction quantitative analysis shows that the weight percentage of EU-1 structure molecular sieve in the composite molecular sieve is 14.9%, and the weight percentage of ZSM-12 structure molecular sieve is 85.1%.

[0048] 3) The EU-1 / ZSM-12 eutectic molecular sieve powder obtained in step 2) was exchanged with 0.75 mol / L NH4Cl solution at a solid-liquid ratio of 1:25 at 85°C for 4 hours, and the ammonium ion exchange was repeated twice. The Na2O% content in the molecular sieve product was less than 0.1%, and an H-type small-grain EU-1 / ZSM-12 eutectic molecular sieve was obtained. The molar ratio of silicon oxide to aluminum oxide was 28.50. The physical and chemical characterization results are shown in Table 1, and it is recorded as EZ12-6.

[0049] Example 8: Preparation of eutectic molecular sieve EZ12-7 1) Preparation of mixed sol: dimethyldimethoxysilane, sodium aluminate, NaOH, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, ethanolamine (in terms of AIDS) and deionized water H2O are uniformly mixed to obtain a mixed sol; in the mixed sol, the alkali source is calculated as Na2O, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is nNa2O:nSiO2:nAl2O3:nOSDA1:nOSDA2:nAIDS:nH2O = 0.25:1:0.005128:0.27:0.03:0.002:25.

[0050] 2) The mixed sol obtained in step 1) is placed in a crystallization kettle, aged at 95°C for 25 hours, then heated to 190°C for crystallization for 36 hours, and after complete crystallization, the solid product is separated, and the solid product is washed, dried at 150°C for 8 hours, and calcined at 750°C for 10 hours to remove the organic template agent, thereby obtaining the original powder of the molecular sieve; the obtained product is analyzed by powder XRD and SEM, and the XRD phase of the original powder after synthesis shows that it has complete characteristic peaks of EU-1 and ZSM-12 molecular sieves, and it is determined to be EU-1 / ZSM-12 eutectic molecular sieve. XRD diffraction quantitative analysis shows that the weight percentage of EU-1 structure molecular sieve in the composite molecular sieve is 89.8%, and the weight percentage of ZSM-12 structure molecular sieve is 10.2%.

[0051] 3) The EU-1 / ZSM-12 eutectic molecular sieve powder obtained in step 2) was exchanged with 0.25 mol / L NH4Cl solution at a solid-liquid ratio of 1:40 at 90°C for 3 hours, and the ammonium ion exchange was repeated twice. The Na2O% content in the molecular sieve product was less than 0.1%, and an H-type small-grain EU-1 / ZSM-12 eutectic molecular sieve was obtained. The molar ratio of silicon oxide to aluminum oxide was 196.30. The physical and chemical characterization results are shown in Table 1, and it is recorded as EZ12-7.

[0052] Example 9: Preparation of eutectic molecular sieve EZ12-8 1) Preparation of mixed sol: Methyldiethoxysilane, aluminum hydroxide, NaOH, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, N,N-dimethylethanolamine (in terms of AIDS) and deionized water H2O are uniformly mixed to obtain a mixed sol; in the mixed sol, the alkali source is calculated as Na2O, the silicon source is calculated as SiO2, and the aluminum source is calculated as Al2O3, and the molar ratio of each material is nNa2O:nSiO2:nAl2O3:nOSDA1:nOSDA2:nAIDS:nH2O = 0.2:1:0.009804:0.0276:0.0324:0.006:20.

[0053] 2) The mixed sol obtained in step 1) is placed in a crystallization kettle, aged at 80°C for 36 hours, then heated to 185°C for crystallization for 24 hours, and after complete crystallization, the solid product is separated, and the solid product is washed, dried at 100°C for 32 hours, and calcined at 550°C for 16 hours to remove the organic template agent, thereby obtaining the original powder of the molecular sieve; the obtained product is analyzed by powder XRD and SEM, and the XRD phase of the original powder after synthesis shows that it has complete characteristic peaks of EU-1 and ZSM-12 molecular sieves, and it is determined to be EU-1 / ZSM-12 eutectic molecular sieve. XRD diffraction quantitative analysis shows that the weight percentage of EU-1 structure molecular sieve in the composite molecular sieve is 45.6%, and the weight percentage of ZSM-12 structure molecular sieve is 54.4%.

[0054] 3) The EU-1 / ZSM-12 eutectic molecular sieve powder obtained in step 2) was exchanged with 1.2 mol / L NH4Cl solution at a solid-liquid ratio of 1:10 at 75°C for 8 hours, and the ammonium ion exchange was repeated twice. The Na2O% content in the molecular sieve product was less than 0.1%, and an H-type small-grain EU-1 / ZSM-12 eutectic molecular sieve was obtained. The molar ratio of silicon oxide to aluminum oxide was 99.0, and the physical and chemical characterization results were shown in Table 1. It was recorded as EZ12-8.

[0055] Table 1 Example Eutectic molecular sieve name Silicon to aluminum ratio <![CDATA[Specific surface area / (m 2 / g)]]> <![CDATA[Mesopore volume, cm 3 / g]]> <![CDATA[Micropore volume, cm 3 / g]]> EU-1 molecular sieve content / % ZSM-12 molecular sieve content / % Example 2 EUZ12-1 147.0 424.6 0.321 0.147 5.8% 94.2% Example 3 EUZ12-2 84.3 411.1 0.294 0.141 29.8% 70.2% Example 4 EUZ12-3 20.4 409.7 0.272 0.136 79.8% 20.2% Example 5 EUZ12-4 52.9 432.9 0.311 0.140 59.6% 40.4% Example 6 EUZ12-5 63.1 393.3 0.312 0.143 54.7% 45.3% Example 7 EUZ12-6 28.5 405.9 0.282 0.146 14.9% 85.1% Example 8 EUZ12-7 196.3 380.7 0.306 0.137 89.8% 10.2% Example 9 EUZ12-8 99.0 356.6 0.262 0.148 45.6% 54.4% It can be observed from Table 1 that the Si / Al ratio of the synthesized eutectic molecular sieves ranges from 20.4 to 196.3, and the BET total specific surface area is >350 m 2 / g, total pore volume>0.26cm 3 / g, micropore volume>0.13cm 3 / g, the content of EU-1 molecular sieve ranges from 5.8% to 89.8%, and the corresponding content of EU-1 molecular sieve ranges from 10.2% to 94.2%. Figures 1 to 4 It can be observed that the EU-1 / ZSM-12 eutectic molecular sieve has characteristic peaks at 7.45±0.2°, 7.91±0.2°, 8.70±0.2°, 19.01±0.2°, 20.52±0.2°, 20.90±0.2°, 22.14±0.2°, 22.96±0.2°, 23.22±0.2°, 23.68±0.2°, 25.78±0.2°, and 27.20±0.2°. Figures 5 to 8 It can be observed that the particle size of EU-1 / ZSM-12 eutectic molecular sieve is <300nm and the grain dispersion is good.

[0056] The above-mentioned embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A nano-sized EU-1 / ZSM-12 eutectic molecular sieve, characterized in that: The XRD phase of the EU-1 / ZSM-12 eutectic molecular sieve has characteristic peaks at 7.45±0.2°, 7.91±0.2°, 8.70±0.2°, 19.01±0.2°, 20.52±0.2°, 20.90±0.2°, 22.14±0.2°, 22.96±0.2°, 23.22±0.2°, 23.68±0.2°, 25.78±0.2°, and 27.20±0.2°.

2. The EU-1 / ZSM-12 eutectic molecular sieve of nano-sized crystals according to claim 1, characterized in that: The eutectic molecular sieve has a crystal length of ≤300nm and a total specific surface area of ​​≥350m 2 / g, total pore volume ≥ 0.24cm 3 / g, in the eutectic molecular sieve, the weight percentage of EU-1 molecular sieve is 5-90%, the weight percentage of ZSM-12 molecular sieve is 10-95%, and the molar ratio of silicon oxide to aluminum oxide in the eutectic molecular sieve is in the range of 20-200; The eutectic molecular sieve is obtained by mixing organosilane, aluminum source, alkali source, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, organic auxiliary agent AIDS and deionized water, and then subjecting the mixture to aging, hydrothermal crystallization, filtration, washing, drying, roasting, ammonium ion exchange, drying and roasting in sequence; The organosilane is calculated as SiO2, the aluminum source is calculated as Al2O3, and the alkali source is calculated as Na2O. The molar ratio of Na2O:SiO2:Al2O3:OSDA1:OSDA2:AIDS:H2O is: (0.05~0.25):1.0:(0.005~0.05):(0.0015~0.27):(0.01~0.3):(0.001~0.01):(10~50).

3. The EU-1 / ZSM-12 eutectic molecular sieve of nano-sized crystals according to claim 2, characterized in that: The aging temperature is 80-120°C, the aging time is 8-36 hours, the temperature of the hydrothermal crystallization reaction is 150-200°C, the hydrothermal crystallization reaction time is 24-168 hours, the temperature of the first drying is 80-150°C, the time is 8-36 h, the roasting temperature is 500-800°C, and the roasting time is 2-20 hours; The drying temperature after sodium ion exchange is 100~140 ℃, the drying time is 12~48 h, the roasting temperature is 500~800 ℃, and the roasting time is 1~10 hours.

4. The nano-sized EU-1 / ZSM-12 eutectic molecular sieve according to claim 3, characterized in that: The synthesis steps of the EU-1 / ZSM-12 eutectic molecular sieve are: S1, preparing a mixed sol: mixing organic silane, an aluminum source, an alkali source, 1,6-bis(methylpyrrolidine)hexane dihydroxide OSDA1, methyltriethylammonium hydroxide OSDA2, an organic auxiliary agent AIDS and deionized water to obtain a mixed sol; S2, placing the mixed sol obtained in step S1 in a crystallization kettle, aging at 80-120°C for 8-36 hours, then heating to 150-200°C for crystallization for 24-168 hours, washing the separated solid product, drying at 80-150°C for 8-36 hours, and calcining at 500-800°C for 2-20 hours to remove the organic template, thereby obtaining a molecular sieve raw powder; S3, the molecular sieve powder obtained in step S2 is subjected to ammonium ion exchange to remove Na + The product is dried at 100-140 °C for 12-48 h and calcined at 500-800 °C for 1-10 hours to obtain the EU-1 / ZSM-12 eutectic molecular sieve.

5. The EU-1 / ZSM-12 eutectic molecular sieve of nano-sized crystals according to any one of claims 1 to 4, characterized in that: The organosilane is at least one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, ethyltriethoxysilane, vinyltriethoxysilane, triethoxysilane, propyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, methyldiethoxysilane, methyltriethoxysilane, trimethoxysilane, propyltriethoxysilane, methylvinyldimethoxysilane, methyldimethoxysilane, isobutyltriethoxysilane, diisopropyldimethoxysilane, and isobutylisopropyldimethoxysilane.

6. The EU-1 / ZSM-12 eutectic molecular sieve of nano-sized crystals according to claim 5, characterized in that: The organic silane is at least one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, trimethoxysilane and triethoxysilane.

7. The EU-1 / ZSM-12 eutectic molecular sieve of nano-sized crystals according to any one of claims 1 to 4, characterized in that: The aluminum source is at least one of pseudo-boehmite, sodium aluminate, aluminum nitrate, aluminum sulfate, aluminum chloride, aluminum hydroxide, aluminum isopropoxide, and SB powder.

8. The EU-1 / ZSM-12 eutectic molecular sieve of nano-sized crystals according to any one of claims 1 to 4, characterized in that: The alkali source is at least one of NaOH, KOH, Na2O2, Na2CO3, and NaHCO3.

9. The EU-1 / ZSM-12 eutectic molecular sieve of nano-sized crystals according to any one of claims 1 to 4, characterized in that the organic auxiliary agent AIDS is any one or more of ethanolamine, N,N-dimethylethanolamine, N-methylmonoethanolamine, N-ethylethanolamine, and N, N-dimethylisopropanolamine.

10. The EU-1 / ZSM-12 eutectic molecular sieve of nano-sized crystals according to any one of claims 1 to 4, characterized in that: In step S3, NH 4+ The ion exchange uses an aqueous solution of an ammonium salt with a concentration of 0.1 to 3.0 mol / L, wherein the ammonium salt is at least one of ammonium chloride, ammonium sulfate, ammonium nitrate, ammonium carbonate, and ammonium acetate; The aqueous solution of ammonium salt and the molecular sieve solid powder are ion exchanged in a water bath at 60~100 ℃ according to the solid-liquid ratio of 1: (4~40), and the exchange is repeated 1~3 times.

Citation Information

Patent Citations

  • Composite molecular sieve with EUO structure and MTW structure as well as preparation method and application of composite molecular sieve

    CN116022821A